1995
DOI: 10.1074/jbc.270.44.26146
|View full text |Cite
|
Sign up to set email alerts
|

Calpain Cleavage of the Cytoplasmic Domain of the Integrin β2 Subunit

Abstract: The cytoplasmic domains of integrin ␤ subunits are involved in bidirectional transmembrane signaling. We report that the cytoplasmic domain of the integrin ␤

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
166
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(170 citation statements)
references
References 44 publications
4
166
0
Order By: Relevance
“…In fact, the cytosolic domain of integrin requires membrane localization to promote apoptosis, 58 and it is possible that calpain-mediated cleavage of the b-integrin cytosolic domain observed in ECM-deprived cells may even act to delay apoptosis by preventing IMD. 72 Despite these differences, the parallels between the APP and integrin systems are compelling, and the functional colocalization of the receptors leaves open the possibility that these elements may act coordinately to regulate the same 'dependence pathway.' A comparison of integrins and canonical dependence receptors is shown in Table 2.…”
Section: Proteolytic Cleavage Of the Integrin Cytosolic Domainmentioning
confidence: 99%
“…In fact, the cytosolic domain of integrin requires membrane localization to promote apoptosis, 58 and it is possible that calpain-mediated cleavage of the b-integrin cytosolic domain observed in ECM-deprived cells may even act to delay apoptosis by preventing IMD. 72 Despite these differences, the parallels between the APP and integrin systems are compelling, and the functional colocalization of the receptors leaves open the possibility that these elements may act coordinately to regulate the same 'dependence pathway.' A comparison of integrins and canonical dependence receptors is shown in Table 2.…”
Section: Proteolytic Cleavage Of the Integrin Cytosolic Domainmentioning
confidence: 99%
“…Calpain induces cleavage of many signaling molecules and cytoskeletal proteins (7, 19 -23). In addition, calpain cleaves the cytoplasmic domain of the ␤ 1 -and ␤ 3 -integrins (24,25). We showed that one of the consequences of calpain activation in cultured cells was the formation of clusters of integrin that appear to contain Rac-binding protein(s) and to be required for the activation of Rac (17).…”
mentioning
confidence: 93%
“…1 (see below), calpain cleaves the cytoplasmic domain of ␤ 3 -integrin at five sites between amino acid residues 735 and 760 (24). Thus, calpain-cleaved integrin in the early integrin clusters would be unable to interact with any molecules requiring this region of the cytoplasmic domain.…”
mentioning
confidence: 99%
“…The hydrophobicity of the N-terminal domain (domain V) has been taken as an indication of its role in membrane anchoring (Kuboki et al, 1987(Kuboki et al, , 1990Inomata et al, 1989Inomata et al, , 1990Lee et al, 1990;Molinari et al, 1994;Moldoveanu et al, 2002Moldoveanu et al, , 2003Khorchid and Ikura, 2002;Pal et al, 2003). Calpains have potential biological functions in apoptosis, the pathology of degenerative diseases, and mediating intracellular calcium signals (Nicotera et al, 1986;Du et al, 1995;Spencer et al, 1995;Arora et al, 1996;Huang and Wang, 2001;Glading et al, 2002). A number of studies indicated that calpains have a role in the cell cycle, specifically in the G 1 to S transition (reviewed in Goll et al, 2003).…”
Section: Introductionmentioning
confidence: 99%